Tactical Vision: Mediation of Tactical Commitment & Moderation of Public Trust in Police Performance - Lof Lasri; Astri Ayu Purwati; Layla Hafni; Mazzlida Mat Deli; Muhammad Luthfi Hamzah (Institut Bisnis dan Teknologi Pelita Indonesia, 2026)
This study investigates the impact of visionary leadership on police performance, emphasizing the mediating role of tactical commitment and the moderating effect of public trust within the context of the Tandun Sector Police (Polsek Tandun), Indonesia. Despite the critical role of sub-district police units in maintaining law and order, challenges such as low case resolution rates, personnel demotivation, and limited community trust have hindered optimal performance. Using a quantitative research design, data were collected from 55 police personnel through total sampling and 55 community members through purposive sampling. Structural analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test direct, indirect, and interaction effects. The results indicate that visionary leadership significantly enhances tactical commitment, which partially mediates its relationship with police performance. Furthermore, public trust strengthens the influence of visionary leadership on operational outcomes, demonstrating its crucial role as a moderating factor. These findings underscore the importance of integrating internal leadership practices with external community engagement to achieve sustainable performance improvements. Theoretically, this research advances policing and public management literature by introducing tactical commitment as a policing-specific construct and positioning public trust as an external legitimizing factor. Practically, the study offers actionable strategies for police leaders to foster tactical readiness, community collaboration, and organizational innovation. Future research is encouraged to explore longitudinal designs, larger samples across multiple regions, and additional variables such as organizational culture and technological adaptation to further enrich the understanding of police performance dynamics.